Aesthetic Experience in Theatre in Non-Formal Education: a Review of Creativity Theory - Syina Dalila; Setyo Yanuartuti; Indar Sabri (Universitas Malahayati Lampung, 2023)
ABSTRACT Failure to foster creativity in learners from an early age will complicate their development at the next age level. This failure can occur due to misconceptions that art teaching should be oriented towards the process and aesthetic experience of learners, but also leads to the demand to become proficient in certain areas of art. An interesting phenomenon is found in the case of non-formal education which is more flexible in managing learning. This study focuses on the review of creativity theory on aesthetic experience in theater distribution in non-formal education. This study aims to find patterns of creation in students in theater learning and the role of educators in providing aesthetic experiences of students through theater learning. Aesthetic experiences in learners are essential to provide in order to achieve meaningful learning. This study uses a qualitative approach to obtain a comprehensive picture of the subject matter, with techniques of collecting data on interviews, observations, and documentation about theater learning in the Banyuwangi Courtyard Theater community. By applying the approach of Miles and Huberman, data analysis techniques are carried out to bring up facts that can provide a more specific view of the phenomenon discussed. Activities in qualitative data analysis are carried out interactively and take place continuously until complete. As a result, the pattern of creation in students in theater learning is a spontaneous response they get in a fun learning. While the role of educators in providing aesthetic experiences to students through theater learning is by fostering student creativity through a psychic approach and recognizing their potential and weaknesses. After educators understand the character of students, then educators can develop appropriate learning strategies, methods, and theories to create a meaningful learning process for maximum outcomes. Keywords: Aesthetic Experience, Theatre, Learning, Creativity, Non-formal Education